Offering a lifestyle intervention to women of premenopausal age as primary prevention for cardiovascular disease? - assessing its cost-effectiveness - Lan Gao; Marj Moodie (BMC, 2022)
Abstract Background There is limited evidence of cost-effective primary prevention interventions for cardiovascular disease (CVD) in young women. This study aimed to assess the value for money of primary prevention of CVD in this population. Methods A Markov microsimulation model consisting of both first-ever and recurrent CVD events was developed to simulate the lifetime intervention impact on cost and health outcomes in women of premenopausal age (30 to 54 years) from the Australian healthcare system perspective. The latest wave of the Australian National Health Survey defined the modelled population's characteristics. The intervention effectiveness of a lifestyle modification program involving changes in diet and physical activity demonstrated to be effective in this population was sourced from a systematic review and meta-analysis. The first-ever and recurrent CVD probabilities were derived from the CVD risk calculators accounting for socio-demographic and clinical characteristics. Costs and utility weights associated with CVD events and long-term management post-CVD were informed by national statistics/published literature. Sensitivity analyses were undertaken to examine the robustness of base case results. Results The lifestyle modification program was associated with both higher costs and benefits (in terms of quality-adjusted life years, QALYs) as a primary prevention measure of CVD in premenopausal women, with an ICER of $96,377/QALY or $130,469/LY. The intervention led to fewer first-ever (N = −19) and recurrent CVD events (N = -23) per 10,000 women over the modelled life horizon. The avoided cost due to reduced hospitalisations (−$24) and management (−$164) of CVD could partially offset the cost associated with the intervention ($1560). Sensitivity analysis indicated that time horizon, starting age of the intervention, discount rate, and intervention effectiveness were the key drivers of the results. If the intervention was scaled up to the national level (N = 502,095 at-risk premenopausal women), the total intervention cost would be $794 million with $95 million in healthcare cost-savings. Conclusion Offering a lifestyle modification program to premenopausal women in Australia as primary prevention of CVD is not cost-effective from a healthcare system perspective. We should continue to search for new or adapt/optimise existing effective and cost-effective primary prevention measures of CVD for women.